Factors Influencing Skin Cancer Preventive Behaviors Based on the Extended Parallel Process Model in Yazd Medical Sciences Students - Seyed Saied Mazloomy Mahmoodabad; Sakineh Gerayllo; Nafiseh Mizani (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Skin cancer is one of the most common cancers and it is mostly caused by ultraviolet radiation. Therefore, this study aimed to investigate the factors affecting skin cancer preventive behaviors in medical sciences students who are responsible for the future health of the community. Methods: This descriptive cross-sectional study was carried out on 150 students who were selected by the simple random sampling method. The data were collected by translating the questionnaire based on the extended parallel process model and were analyzed using SPSS-18 software. Moreover, data coding was analyzed using appropriate nonparametric statistical tests. Results: The mean age of participants was 22.01 ± 5.24, more than half of whom (57.3%) used sunscreen as a self-protective behavior against the sunlight. The perceived severity construct had the highest score among the constructs. Among the background variables, gender had a significant statistical difference with the constructs of fear and behavioral intention, and preventive behaviors and economic status variable in the perceived response efficacy construct. Among the model constructs, the behavioral intention was the strongest behavioral predictor of skin cancer prevention. Conclusion: Considering the correlation between self-efficacy and behavior as well as the correlation between the perceived response efficacy and behavioral intentions, it seems necessary to plan in this field in order to increase protective behaviors against sunlight and skin cancer prevention by removing existing barriers including cultural issues.